(untitled) (Research, Society and Development, 2020)
Objectives: To present the academic production of the Nursing Education and Health Research Center of the Anna Nery Nursing School, in the strictu sensu Postgraduate course, in the 2007 to 2019 temporal study and to analyze the product coming from this construction for Nursing and training in Nursing. Method: quantitative, descriptive research carried out, through documentary analysis of dissertations and theses defended. Data collected through the reading of abstracts and full texts. Results: 51 studies were advocated. All the studies used the qualitative methodology, the hospital scenario represented 46% of the studies and the interview technique was used in 31 studies. There were 38 articles and 2 books published. Conclusion: The Center showed consolidation and potency in the construction of knowledge in Nursing Education through the discussion of topics related to population health and nursing care, as well as the process that permeates the educational system and Nursing education.